The impact of Crisis Communication on audience: A study based on plane crash - Chan, Calvin (2007)
Organisational crises have now become as common as having a cold. Crises negatively affect the company's reputation and share price. Maintaining a reputation has today become paramount. Therefore, post-crisis communication is absolutely essential and has to be planned carefully. Poor crisis communication would leave the audience or the public with bad impression over the company. The poor crisis communication may even extend the bad impression over the whole industry. In responding to this situation, the main purpose of this research is to investigate the impression of the audience against different crisis communication strategies used by companies. Ninety-nine individuals from Hong Kong were invited and responded to a hypothetical scenario describing a plane crash. The scenario involved three kinds of crisis communication strategies: (1) shift the blame; (2) no comment; and (3) apology, which are commonly used by companies. Results showed that the audience's impressions of the company were significantly affected by the crisis communication strategy adopted, of which apology was preferable. However, the response of a single company did not cause the audience to form a bad impression against the whole industry. Implications of the findings for impression management, crisis communication and cross-cultural research are discussed.